The role of Islamic micro finance institutions (MFI) in increasing farmer's revenue - Tarmizi, Mulya; Effendi, Jaenal (Journal of Islamic Economics Lariba, 2017)
Poor people in Indonesia are mostly found in village region. 63% of the total poor people in Indonesia and majority of village people work as a farmer. The role of Islamic Microfinance Institution such as Islamic Cooperative is to increase the farmers income who has been the member of its cooperative. The purposes of the research are to analyze the difference of farmers’ income before and after applying the equity-based financing to islamic microfinance institution by using Paired T Test, and analyze which factors were affecting the farmers’ income in case study of farmers as the member of Islamic Cooperative Al-Ittifaq and used Ordinary Least Square method. The result shows that Islamic microfinance program signifcantly and positively affect the farmers income. The variables that significantly affect the income are size of financing taken by respondents, duration of membership, distance between farmer’s house and cooperative, and background of farmers’ education.